Identidades em movimento: a representação feminina e as relações de gênero na obra de Angela Carter - Rodrigues, Talita Annunciato [UNESP] (2015)
This research aims to analyze the representation of women and gender relations in the work of British writer Angela Carter (1940 - 1992). Turning to various literary forms such as myths, fairy tales and science fiction, Carter proposes the questioning of images and stories in our society which form the basis of our culture and the relationship between men and women. One can observe in her narratives a proposal for a revaluation of women's experiences, problematized through the characters' journey within the universe in which they are confined. In Carter's novels, the characters are placed in roles that they had to take, either freely or imposed by other characters, and the identity is exposed as performance, or a series of roles or appearances. Therefore, we defend the thesis that, by denying a fixed identity for her characters, the author proposes a constant process of building themselves, questioning notions such as essentialism and the values imposed by the patriarchal model of society. In this sense, we consider that female identity and gender relations are constantly questioned and ressignified in Angela Carter's novels. For this purpose, we take as theoretical basis feminist criticism and gender studies, which present themselves as ways to reflect on human condition in the literary text, questioning the constructions of femininity and masculinity present in the social strata. Initially, this paper presents a brief investigation into Carter's life and work and her relationship with the creative process as a way to understand the dialogue between the author's critical attitude and her fiction. After situating her writing in the context of contemporary female authors, we explore how female representation is developed in Carter's novels in general, passing then to a further analysis comparing two of her narratives: Heroes and Villains (1969) e The Passion of New Eve (1977)